PERFORMANCE QUALITY OF EMPLOYEES WHEN WORK FROM HOME: AN ANALYSIS OF EMPLOYEE COMPETENCY DURING THE COVID-19 PANDEMIC - Wandy Zulkarnaen (Komitmen: Jurnal Ilmiah Manajemen, 2021)
In this era, every company will definitely try to increase company productivity. Therefore companies really need Human Resources because every company company will compete fiercely in developing or improving the quality of their company. Especially with the current conditions with the emergence of Covid-19, companies will try to find employees who have good competencies and abilities. Data released by LIPI states that as many as 63.8% of employees do WFH. Based on the background, this research will analyze the competence of employees' performance in conducting WFH during the Covid-19 pandemic. The data used in this paper is secondary data obtained by the author through various literatures. The result of the research is the need for someone's competence in working anywhere or in any field. This includes being in a pandemic and working with the WFH system. Therefore, employees must develop the competencies that exist within themselves and continue to show good performance.